Contextual Science Learning Through Mangrove Ecosystems: A Needs Analysis for Elementary Education - Zenny Taufikurrizal; Isnawati Isnawati; Tarzan Purnomo; Endang Susantini; Fida Rachmadiarti; Abdul Hasan (Yayasan Keluarga Guru Mandiri, 2026)
This study analyzes elementary school learning needs based on the local potential of the Tuban Mangrove Center to strengthen students' scientific literacy in ecosystem topics. This study was motivated by the persistently low level of students' scientific literacy, largely attributed to concept-oriented instruction that insufficiently contextualizes learning within authentic real-world situations. A qualitative needs analysis design was employed involving six elementary school teachers and three purposively selected mangrove center managers. Data were gathered through semi-structured interviews, classroom observations, and analysis of instructional documents. Instrument validity was established through expert judgment, while data trustworthiness was enhanced using source and technique triangulation. Data analysis followed the Miles and Huberman interactive model comprising data reduction, data display, and conclusion drawing. The findings reveal that science learning is largely textbook-oriented and has not effectively utilized the environment as a learning resource. Limited laboratory facilities and the absence of contextual teaching materials contribute to low authentic learning experiences. Although the Tuban Mangrove Center has strong potential as a natural laboratory for scientific observation and investigation, its use remains unsystematic. This study highlights the need for structured, contextual learning designs based on local potential to enhance students' scientific literacy and ecological awareness.